Human Resources Optimization (Case Study on Private Company in Palembang City) - Ahmad Yani Kosali (Indonesian Journal of Business Analytics, 2021)
This research uses qualitative research techniques with a case study approach. Data obtained through interviews, observation, and document review. The technique of selecting informants is carried out purposively (purposive sampling) based on certain characteristics, namely (1) Working in a private company, (2) Having at least one year experience as a manager, (3) Carrying out human resource management functions. The instrument in this study was the researcher himself as the main data collection tool. The purpose of this study was to determine the optimization of Human Resources in private companies in the city of Palembang. The results of this study indicate that human resources (employees) are company assets, which are the main support for organizational goals. Potential human resources need to be maintained by continuing to develop employee competencies and skills. The development program implemented by PT. Karya Makmur and PT. Tugu Mandiri Jaya in the form of training carried out based on NAT (Need Analysis Training). PT. Karya Makmur applies various training techniques, including: case studies, roleplaying, and a lecture system. Meanwhile, PT. Tugu Mandiri Jaya applies training techniques such as: in-service training, vestibule training, and simulation.